A Structural Equation Modeling of Empathic Leadership of School Administrators Affecting Teacher Well-Being under Khon Kaen Primary Educational Service Area Office 2 - Chuenwatthana, Korawit; Sirisooksilp, Saowanee (Journal of Education Studies, Chulalongkorn University, 2024)
The research objectives were to: 1) examine the congruence and analyze the influence of variables of a structural equation model of school administrators’ empathic leadership affecting teacher well-being with empirical data, and 2) develop guidelines for developing empathic leadership among school administrators. This mixed method research study comprised two phases: 1) examining the coherence and analyzing the influence of the model by selecting a sample group of 220 school administrators and teachers selected via a multistage sampling approach. Data were gathered using a closed-end questions related to school administrators’ empathic leadership and teacher well-being and subsequently analyzed using SEM statistics by SPSS and Mplus; and 2) developing guidelines for developing the empathic leadership of school administrators. This involved interviewing 5 qualified individuals using a semi-structured interview format as the data collection tool. The collected data were analyzed through content analysis. The research results are summarized as follows: 1) the structural equation modeling of empathic leadership of school administrators affecting teacher well-being was correlated with empirical data (χ 2= 33.292, df = 23, p-value = 0.0761, CFI = 0.993, TLI = 0.986, RMSEA = 0.045, SRMR = 0.047) and empathic leadership had a positive influence on teacher well-being, with a direct influence weight of 0.833 at the 0.01 level; and 2) the guidelines for developing the empathic leadership of school administrators comprised 13 items, outlining compliance with key elements of empathic leadership, and received the highest level of evaluation results.